Quality of intrapartum and newborn care in Tigray, Northern Ethiopia - Girmatsion Fisseha; Yemane Berhane; Alemayehu Worku (BMC, 2019)
Abstract Background Quality intrapartum and newborn care is considered to be poor in Sub-Saharan Africa. However, studies done in Ethiopia are limited. Therefore, this study was conducted to assess the magnitude and factors associated with quality intrapartum and newborn care in Tigray, Northern Ethiopia. Methods Facility based survey was conducted from December 2014 to February 2015 in Tigray, Northern Ethiopia. The quality of intrapartum care provided by a total of 106 skilled birth attendants to 216 labouring mothers and newborns were observed during childbirth in the health facilities. Standardized questionnaires and checklist were utilized to collect data. Quality of intrapartum service was measured using standard intrapartum criteria. Thus, good quality service was considered if the mother and newborn scored 75% or more of the intrapartum criteria during childbirth. Binary and multiple logistic regression model was used to determine the factors associated with quality intrapartum and newborn care services. Results 29.2% of mothers and 67.6% newborns received good quality care during intrapartum and immediate postpartum periods respectively. However, only 47.2% of mothers and newborns received a friendly care during childbirths. The independent predictors of quality intrapartum and newborn care were the appropriate use of partograph (AOR 3.92; 95% CI 1.78, 8.63), friendly maternal and newborn care services (AOR 7.9; 95% CI 3.59, 17.33), more than two years working experience (AOR 0.31; 95% CI 0.13, 0.73) and using services in different Zones in the study area. Conclusions The quality intrapartum care is poor in the study area and it is associated with inappropriate use of partograph, unfriendly care, and experience of health providers. Scaling up obstetric service, continuous training and motivation of service providers and revising the criterion for accreditation of service providers are important.